Growing Pains of Industrial Renewal – Case Nordic Cleantech - Antti-Jussi Tahvanainen; Peter Adriaens; Annu Kotiranta (The Research Institute of the Finnish Economy (ETLA), 2016)
To steer economies onto a sustainable path in a way that is compatible with the urgent priorities of economic developers, sustainability needs to come with new business opportunities, growing markets and, most importantly, new jobs. The big question becomes then how do you wed economic growth with sustainability? Enter the growth of cleantech and the emergence of green industries. Recent rankings place Finland in the top-3 of global leaders in cleantech, along with Israel and the US. Driven by an ambition to selectively invest in a `green' economic turnaround, a number of strategy-level research documents and roadmaps have been produced in recent years on how to kindle new growth and create jobs in the Finnish CleanTech- and the Bio-economies. The three industry ecosystems frequently mentioned are efficient energy solutions (smart grid), mobility-as-a-service (smart mobility), and the bioeconomy. The ultimate questions to be answered are: In which industry ecosystems does Finland have the necessary assets to be an effective competitive contender? And given the existing asset base, what is the true potential of these sectors as engines of economic growth? To rise to the challenge, the report probes (a) the structure and direction of industrial activity that underlie the selected ecosystems, (b) the value capture potential of individual companies in them, and (c) the types of financing the companies are most compatible with. The results are somewhat sobering. They clearly show that for business and economic development purposes the only feasible approach to Cleantech is to deal with it by the ecosystem. The three ecosystems analyzed in this study all feature different industrial structures, make vastly different value propositions, address different markets and involve a very different set of stakeholders. There is little value in cursorily lumping them together under a quasi-common concept such as Cleantech or the Bioeconomy. These concepts have no substance as they do not refer to specific industrial or economic activity. Hence, it is also very challenging to develop concrete instruments for economic or business development purposes that are to promote such activity. At worst, scarce resources are put to suboptimal use, as they are allocated over a vast spread of individual companies and projects that might be a fit with the overall theme of Cleantech but have no common denominator in the form of an industrial ecosystem and its underlying value chains. Our results on a next to non-existent Bioeconomy provide for an excellent showcase. We further show that even the more promising ecosystems such as Smart Mobility and Smart Grids are in the throes of growing pains. There is much that economic developers can do efficiently to alleviate them. The poor leverageability of industry assets and connections for market access across the board speak of fragile, budding industry structures that make it difficult for companies to establish robust markets and steady businesses in the short term. Companies of different sizes suffer the symptoms in their own ways. On the one hand, large incumbents do wield the assets necessary to conquer the ecosystem – telecommunications operators seem to have an especially favorable vantage point in smart ecosystems – but shoot themselves in the foot by applying conventional, capital-intensive business models that leave the door open for more agile growth companies that harness the potential of digitalization to exploit opportunities. On the other, start-ups and SMEs indeed show the drive and lean on nimble enough business models but utterly lack the assets for a full-scale conquest. It is easy to envision a symbiotic relationship, in which incumbents provide the capital-intensive assets while their smaller peers introduce the competitive business models. Given the incipient structure of the ecosystems, however, just finding appropriate partners can incur considerable transaction costs. Here economic developers can step in, helping to find matches via collaborative accelerators that broker partnerships between industrial heavy-hitters on a mission of industrial renewal and small growth companies looking for resources and downstream assets. Finding partners is a formidable challenge in and by itself, but our conclusions point to even more systemic impediments to industrial renewal that lie outside the industry's sphere of influence. One such is the lack of proper standards for the interconnectivity and interoperability of the various, often proprietary, IT systems that the numerous stakeholders to ecosystems run their businesses on. Especially smart ecosystems by definition build on the seamless interoperability across diverse system architectures and organizational boundaries. In the absence of universal standards, interconnectivity needs to be established one relationship at a time, building on contractually agreed, customized solutions that do not scale beyond the specific relationship. Economic developers can considerably speed up the construction of a digital business environment by introducing universal standards that promote the emergence of plug-and-play platforms for efficient interoperability. In a world of autonomous, self-driving vehicles and applications that affect offtake and feed into electricity grids, quality and safety controls for algorithms that govern these systems will be paramount for individual and societal safety.
Keywords: O11; O14; O25; O33; O38; O41; O44; 330; Cleantech; Value capture; Industrial renewal; Industrial ecosystem; Investability; Sustainable growth; Smart grid; Smart mobility; Bioeconomy; Umwelttechnik; Nachhaltige Entwicklung; Geschäftsmodell; Betriebliche Wertschöpfung; Nachhaltige Mobilität; Biotechnologie; Bioökonomik; Finnland